2016
DOI: 10.1177/1847980416669488
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of antioxidant and skin moisturizing effects of olive oil by incorporation into microemulsions

Abstract: The aims of the present study were to develop olive oil microemulsions and characterize their antioxidant and skin moisturizing properties. The acid, iodine, and saponification values of olive oil were 0.38 + 0.01 mg potassium hydroxide/g, 88.2 + 5.9 mg iodine/g, and 192.2 + 1.4 mg potassium hydroxide/g, respectively. Pseudoternary phase diagrams, constructed using the water titration method, produced suitable microemulsions: microemulsion 1 (10% olive oil, 64% Tween 85, 16% propylene glycol, and 10% water) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 37 publications
2
11
1
Order By: Relevance
“…The replacement of -NH groups by -COO groups in the CMCH structure was previously reported to be beneficial not only to level of solubility, but also antioxidant activities [ 43 ]. Although some studies suggested the effects of molecular weights to FRAP antioxidant activities [ 44 ], such effect was not evident in current study.…”
Section: Resultscontrasting
confidence: 68%
“…The replacement of -NH groups by -COO groups in the CMCH structure was previously reported to be beneficial not only to level of solubility, but also antioxidant activities [ 43 ]. Although some studies suggested the effects of molecular weights to FRAP antioxidant activities [ 44 ], such effect was not evident in current study.…”
Section: Resultscontrasting
confidence: 68%
“…myrcene and citral) to which the inhibitory effect had been previously ascribed, it is plausible that the anti‐tyrosinase activity of our sample might depend on some other constituents. In this regard, it is worth mentioning that a recent study found a significant anti‐tyrosinase activity in citrus EOs which contained very low levels of myrcene and citral, but was extremely rich in limonene, as was C . aurantium EO 1.…”
Section: Resultsmentioning
confidence: 98%
“…The higher activity of the formulations relative to the oil dilutions was probably due to the incorporation of the oil into the formulation, which may influence its behavior (Hamed et al 2012;Chaiyana et al 2014). Although the antioxidant activity of the formulations was higher then that of the diluted oil, it was not as high as that of microemulsions with olive oil (Chaiyana et al 2016). The choice of the carrier can either increase or decrease the potential antioxidant activity of the microemulsion, thus the choice of surfactant is important, since these substances may or may not present antioxidant activity when isolated (Kim et al 2009;Pérez-Rosés et al 2014).…”
Section: Acta Amazonicamentioning
confidence: 94%